Is risk the fuel of the business cycle? Financial frictions and oil market disturbances - Christoph Schult (Halle Institute for Economic Research (IWH), 2024)
I estimate a dynamic stochastic general equilibrium (DSGE) model for the United States that incorporates oil market shocks and risk shocks working through credit market frictions. The findings of this analysis indicate that risk shocks play a crucial role during the Great Recession and the Dot-Com bubble but not during other economic downturns. Credit market frictions do not amplify persistent oil market shocks. This result holds as long as entry and exit rates of entrepreneurs are independent of the business cycle.
Keywords: E32; E37; E44; Q43; 330; financial frictions; NK-DSGE models; oil price; recessions; risk